O Livro Didático De Língua Portuguesa E As Novas Tecnologias: Uma Análise Comparativa Entre Livro Impresso E Digital - Hott, Juliana Souza Lopes [UNIFESP] (2017)
This dissertation is part of the research field of Applied Linguistics and aims to perform a comparative analysis between the printed and digital versions of a High School textbooks collection, approved by the ProgramaNacional do LivroDidático (PNLD) 2015, in order to understand the similarities and distances between the printed textbook and the digital book. The corpus of the research is the collection of the PNLD 2015, composed of printed and digital books: Português: linguagensemconexão, volumes 1, 2 e 3, published by the publishing company Leya in 2013, the only digital book collection approved by the Program. We begin with the guiding idea that the digital textbook can promote a greater interaction of the subject in relation to the printed book, pursuant to raising a greater autonomy for the subject in the construction of the discourse. We sought to analyze whether the digital textbook approved by PNLD 2015 promotes interaction and, consequently, makes the teaching and learning process more meaningful for the involved agents. In addition, we observe how this digital book converges and diverges from the printed book, showing whether it is in fact a digital book or just a digital print. In the development of the research, it was necessary, initially, to carry out a vast theoretical study that would allow us to have a parameter of the characteristics that a digital textbook could cover, given the few academic and theoretical studies developed in this respect. From this discussion, we think the categories and characteristics to be analyzed in the corpus of this research. We analyze the three books that make up the Collection, in their printed and digital versions. We analyze the software of the digital books and the interfaces, as well as the ObjetosEducacionaisDigitais (OED) that compose it, comparing them with the printed books. We also consider how the use and working of language in these materials is processed. From this analysis, we conclude that the digital book can not be seen as a mere digitization of the printed book, although most of its contents and structure are based on this digitization. However, the material still does not encompass the characteristics necessary to be considered as an interactive digital textbook. It has a few features that complement the printed book, but it is still quite restricted. We believe, therefore, to be a book that is on the way to being a digital textbook.